Creative Digital Art Illustration: Prince Dhammathibet (Chao Fah Kung)’s Kap He Ruea (Royal Ship Lyrics) - Nakhoncharupong, Charuwan; Lampao, Kanchana (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
Witnessing peafowls gracefully dance, Contemplating the allure of the Golden rod’s glance, An adornment of elegance, a cherished stance, Like a beloved, a cherished romance... The literary opus authored by Prince Dhammathibet, known as “Chao Fah Kung,” epitomizes a lyrical composition that splendidly showcases the magnificence of the royal barge procession. It encapsulates profound sentiments and emotions evoked as the monarch conveys the essence of nature, embracing both sides of the journey during his royal barge to pay homage to the Buddha’s footprint at Saraburi. This poetic masterpiece reveres the beauty of nature, encompassing its aquatic marvels, arboreal wonders, and avian inhabitants. Every section exudes a profound sense of affection for women, exemplified by the poetic admiration of birds (Bott Hae Chom Nok), metaphorically likening the beloved woman to the graceful peafowl. The sight of the peafowl’s elegant tail in rhythmic motion conjures vivid memories of the king’s beloved woman, intertwined with their moments of blissful dance. “Kap Hae Rua,” the royal barge procession’s boat songs authored by Prince Dhammathibet (Chao Fah Kung), is esteemed as a precious masterpiece, deserving the esteemed readership of Thais. It masterfully delineates the captivating allure and scenic grandeur inherent in the royal boat procession. This melodious epic poem weaves a tapestry of enchanting words, employing metaphors and poetic devices that engage and captivate the reader. It serves as a poignant reflection of the Thai way of life during the late Ayutthaya period, a time when water transport played a role in society. Its narrative imparts a comprehensive understanding of boat processions, customs, traditions, and the profound appreciation for the inherent beauty of women. The meticulous illustration of manuscripts or books plays a pivotal role in accurately preserving the historical narratives. These visual depictions carry immense significance, effectively conveying, safeguarding, and perpetuating the aesthetic beauty embedded within the local context of each era. With the advent of modern technology, digital art emerges as the paramount medium for crafting vivid and impactful representations of historical events, preserving their allure in a clear